"The fad for Polygonum will fade away!": historic aspects of the propagation and success in France of the Reynoutria complex based on archives. Issue 3 (2nd July 2020) - Thiébaut, Mélanie; Nicolas, Sébastien; Piola, Florence
ABSTRACT: Japanese Knotweeds were introduced by man during the 19 th century in Europe, where they hybridized and formed a species complex now considered as "invasive". On the basis of many herbarium specimens, the literature and archive documents, we describe the history of their discovery and introduction in France. The circumstances of their hybridization are given, as well as the reasons for the spread of the complex composed of both taxa and their polyploid hybrids. We show that after its discovery by Von Siebold, Reynoutria japonica was introduced as a single male-sterile clone in Lorraine during the early 1850s, whereas R. sachalinensis was discovered by both the French and Russians and subject to successive introductions. Our study reveals that at the end of the 19 th century, these Asiatic Knotweeds became very popular among horticulturists and botanical gardens. Their cultivation in sympatry has led to the production of their hybrid R . x bohemica, as well as interspecific hybridizations and introgressions with parental species, leading to considerable genetic diversity, escape and naturalisation.